A systematic literature review on the effects of bullying at school - Tharishini a/p Mana Mohan; Abu Yazid Abu Bakar (SCHOULID: Indonesian Journal of School Counseling, 2021)
Bullying is a severe problem that is experienced, especially in schools. Children belong to the same social group, but some feel powerful than others and therefore take advantage of them to physically or verbally abuse them. Many institutions are aware, but most cases are not handled because most victims do not report. Therefore, only physical bullying is addressed as the impacts can be easily seen by adults. Various articles were analyzed to illustrate the different effects of bullying on the bully, the victim, and those around. The results demonstrate that bullying results in emotional, physical, and health effects and affects a victim's academic performance.